2023
DOI: 10.1371/journal.pone.0284168
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline’s anticholinergic adverse drug reactions–A systematic multiple-indication review and meta-analysis

Abstract: Background Half the US population uses drugs with anticholinergic properties. Their potential harms may outweigh their benefits. Amitriptyline is among the most frequently prescribed anticholinergic medicinal products, is used for multiple indications, and rated as strongly anticholinergic. Our objective was to explore and quantify (anticholinergic) adverse drug reactions (ADRs) in patients taking amitriptyline vs. placebo in randomized controlled trials (RCTs) involving adults and healthy individuals. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…As regarding pharmacological preventive treatment for TTH, the tricyclic antidepressant amitriptyline is considered as first-line option, followed by mirtazapine and venlafaxine as second and third options [ 2 ]. However, the effects of these prophylactic drugs may be limited and treatment may be complicated by side effects including dizziness, somnolence, weight gain, and gastrointestinal disorders [ 2 , 14 , [35] , [36] , [37] , [38] ]. Evidence of high quality showed that acupuncture was comparable to amitriptyline in number of patients needed to treat for a patient to have a beneficial outcome (number needed to treat [NNT], 11 vs 12) with a higher number of patients needed to treat for a patient to have an adverse event (number needed to harm [NNH], acupuncture vs amitriptyline, 20 vs 2 [1.6 to 2.6]) [ 14 , 19 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…As regarding pharmacological preventive treatment for TTH, the tricyclic antidepressant amitriptyline is considered as first-line option, followed by mirtazapine and venlafaxine as second and third options [ 2 ]. However, the effects of these prophylactic drugs may be limited and treatment may be complicated by side effects including dizziness, somnolence, weight gain, and gastrointestinal disorders [ 2 , 14 , [35] , [36] , [37] , [38] ]. Evidence of high quality showed that acupuncture was comparable to amitriptyline in number of patients needed to treat for a patient to have a beneficial outcome (number needed to treat [NNT], 11 vs 12) with a higher number of patients needed to treat for a patient to have an adverse event (number needed to harm [NNH], acupuncture vs amitriptyline, 20 vs 2 [1.6 to 2.6]) [ 14 , 19 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…As anti-muscarinic medication, systemically administered amitriptyline led to typical anticholinergic side effects, such as cconstipation, dry mouth, dry eyes, urinary retention and so on (e.g. [ 35 ]). These effects paved the way for new, more selective and highly compatible antidepressants, like SSRIs and SNRIs.…”
Section: Discussionmentioning
confidence: 99%
“…Another 2018 systematic review of patients older than 60 years reported that urological medications had an association with dry mouth (OR for oxybutynin, 18.9 [95% CI, 8.4 to 42.2]; OR for darifenacin, 7.4 [95% CI, 2.9 to 19.2]; OR for fesoterodine, 6.9 [95% CI, 3.6 to 13.4]; OR for solifenacin, 5.3 [95% CI, 2.0 to 14.5]; OR for tolterodine, 4.8 [95% CI, 3.3 to 7.2]; and OR for mirabegron, 1.2 [95% CI, 0.5 to 2.9]), followed by antidepressants (OR, 4.7 [95% CI, 2.7 to 8.3]), and psycholeptics (OR, 2.6 [95% CI, 1.8 to 4.0]) . In particular, a 2023 systematic review and meta-analysis of 9 RCTs (2499 patients) of amitriptyline used for depression, pain, or functional dyspepsia (dose ranges, 5 mg to 300 mg) vs placebo reported that dry mouth was more frequent in patients taking amitriptyline (risk difference, 52.1%; OR, 11.10 [95% CI, 6.5 to 19.1]) . Other medications or conditions that are associated with increased risk of salivary gland hypofunction include immune checkpoints inhibitors (CTLA-4, PD-1, and PD-L1 inhibitors), radiation therapy for head and neck cancers, dehydration, oral chronic graft-vs-host-disease, and Sjögren disease …”
Section: Methodsmentioning
confidence: 99%
“…8 In particular, a 2023 systematic review and meta-analysis of 9 RCTs (2499 patients) of amitriptyline used for depression, pain, or functional dyspepsia (dose ranges, 5 mg to 300 mg) vs placebo reported that dry mouth was more frequent in patients taking amitriptyline (risk difference, 52.1%; OR, 11.10 [95% CI, 6.5 to 19.1]). 9 Other medications or conditions that are Dry mouth is a common condition that can result from certain medications (anticholinergics, antihypertensives, antihistamines, antipsychotics, sedatives, immune checkpoint inhibitors, and antidepressants), radiation therapy for head and neck cancers, aging, and autoimmune diseases such as Sjögren disease. Dry mouth can lead to increased risk of dental caries, oral infections, and difficulty in speaking and swallowing.…”
Section: Clinical Presentation and Epidemiologymentioning
confidence: 99%